Measuring outdoor recreationists' beliefs in climate change: Testing the Occurrence and Anthropogenic Causation Scale (OC-AN). (October 2015) - Brownlee, Matthew T.J.; Verbos, Rose I.
Abstract: Outdoor recreation areas are impacted by novel changes in climate. Consequently, nature centers and national parks often deliver climate change education. Recreationists' beliefs in climate change are important to understand because effective education relies on understanding an audience's beliefs. However, measuring beliefs in climate change is complicated because the phrase 'global climate change' elicits diverse meanings that are unstable across groups of outdoor recreationists. Without valid measures to identify outdoor recreationists' beliefs in climate change, it is difficult to understand their beliefs and deliver effective education. Therefore, researchers developed and tested two scales to create the Occurrence and Anthropogenic Causation Scale (OC-AN). This scale measures the two primary dimensions of climate change beliefs: (1) Occurrence (OC; belief that climate change is currently happening), and (2) Anthropogenic Causation (AN; belief that climate change is caused by humans). Researchers tested the scale's performance across three populations: (1) national park visitors in Alaska ( n =429), (2) lake recreationists in the southeast U.S. ( n =210), and (3) marine recreationists along the U.S. Atlantic Coast ( n =483). The OC-AN maintained appropriate metric invariance, exhibited high validity, and demonstrated appropriate sensitivity across these diverse groups. Management implications: First, managers and researchers can use the OC-AN Scale to understand the levels of beliefs in Occurrence and Anthropogenic Causation, which can provide necessary baseline data for park managers and educators to understand their visiting audience. Second, the OC-AN can also be used to understand outcomes of a climate change education experience or outdoor recreationists' interactions with climate-influenced resources (e.g., Brownlee, Hallo, Wright, Moore, & Powell, 2013 ). Third, the OC-AN could also be applied longitudinally to track changes in a particular group's beliefs over time. Furthermore, although the OC-AN requires further testing, it is likely that the scale could be applied to the general public or other specialized groups who are not outdoor recreationists. Finally, the individual items that comprise the OC-AN and the mean responses may inform climate change messaging designed for a specific sub-population.